2018
DOI: 10.1613/jair.5637
|View full text |Cite
|
Sign up to set email alerts
|

Bisimulations on Data Graphs

Abstract: Bisimulation provides structural conditions to characterize indistinguishability from an external observer between nodes on labeled graphs. It is a fundamental notion used in many areas, such as verification, graph-structured databases, and constraint satisfaction. However, several current applications use graphs where nodes also contain data (the so called "data graphs"), and where observers can test for equality or inequality of data values (e.g., asking the attribute 'name' of a node to be different from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In particular, in this article we consider arbitrary data graphs as models for XPath = . Data graphs are the underlying mathematical structure in graph databases (see, e.g., [LV12,RWE13,AG08]) and it is important to study the metalogical properties of languages to query this particular kind of models (see, e.g., [LMV16,ABFF18]). In this respect, we focus on a variant of XPath = which provides us with several interesting expressivity features.…”
Section: Xpath As a Modal Logic With Data Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, in this article we consider arbitrary data graphs as models for XPath = . Data graphs are the underlying mathematical structure in graph databases (see, e.g., [LV12,RWE13,AG08]) and it is important to study the metalogical properties of languages to query this particular kind of models (see, e.g., [LMV16,ABFF18]). In this respect, we focus on a variant of XPath = which provides us with several interesting expressivity features.…”
Section: Xpath As a Modal Logic With Data Testsmentioning
confidence: 99%
“…Bisimulation for XPath on data trees was investigated in [FFA14,FFA15]. In [ABFF16,ABFF18] it is shown that the same notion can be used in arbitrary models. It is simple to extend these definitions to take into account hybrid operators (see, e.g., [ABM01,BdRV01]).…”
Section: A Note On Bisimulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For an overview on the expressiveness and evaluation of XPath, we refer the reader to [Benedikt and Koch 2008;Bojańczyk and Parys 2011]. The problem of testing for bisimulation in this setting has also been addressed in [Abriola et al 2016;Figueira et al 2015]. Axiomatizations and calculi for XPath have been proposed in [Baelde et al 2016;Abriola et al 2017a;Areces et al 2017;Areces and Fervari 2016].…”
Section: Other Formalisms For Trees With Data Valuesmentioning
confidence: 99%
“…The most impressive application works deal with movie actor indexing, but it is worth noting that the prior knowledge of appearance models for a cast [13] and the number of searching clusters (i.e. the number of characters) makes the task easier [1]. Besides, support by existing video captions [27] or other contextual knowledge is required [3].…”
Section: Introductionmentioning
confidence: 99%